UKRAINE BETWEEN NATO AND RUSSIA (Годишен зборник на Филозофски факултет - Скопје, 2023)
In the past two decades, Ukraine has significantly deepened its relations with NATO. Following Russia’s seizure of Crimea and instigation of conflict in the eastern Ukrainian region of Donbas in 2014, Ukraine’s interest in NATO entry has particularly intensified. According to public opinion polls in Ukraine, membership in the Alliance is critical to the country’s security. On the other hand, Russia presents the further expansion of NATO to the east as the main threat to its national security. The current developments on the ground and the ongoing war between Ukraine and Russia will affect NATO’s attitude towards Ukraine’s membership prospects in the Alliance. The potential for further escalation of the war in Ukraine is significant, although it is more likely that the war will flare up and target Ukrainian forces and the civilian population, but the likelihood of the involvement of the Western Allies in the conflict is also more certain. Ukrainian authorities will have to limit their expectations for NATO membership and focus only on maximum cooperation with the Alliance.